Vitamin D Supplementation Improves Handgrip Strength in Postmenopausal Women: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zhang, Jia-Li; Poon, Christina Chui-Wa; Wong, Man-Sau; Li, Wen-Xiong; Guo, Yi-Xun; Zhang, Yan (Frontiers in Endocrinology, 2022)
Introduction: In postmenopausal women, vitamin D deficiency (as defined by the circulating level of 25(OH)D being below 20 ng/mL (50 nmol/L)) is a regular occurrence. The effect of vitamin D supplementation on the muscle function of postmenopausal women has been controversial. This systematic review and meta-analysis of randomized controlled trials (RCTs) examines and summarizes the effects of vitamin D supplementation on the muscular strength and mobility of postmenopausal women. Methods: RCTs that met the inclusion criteria for this study were identified by searching PubMed, EMBASE, and the Cochrane Library. Postmenopausal women who were included in the study were exposed to RCTs assessing the effectiveness of vitamin D supplements. Meta-analysis data were extracted by two independent reviewers and screened for methodological quality. RCTs that did not meet the minimum requirement for assessment were excluded. By the meta-analysis, effect size (weighted mean differences, WMD) of handgrip strength (HGS) and timed-up and go test (TUG) with 95% confidence interval (CI) was obtained to compare reported results across the included RCTs. Results: A total of 19 trials were included in this systematic review, among which 13 trials were eligible for the meta-analysis. In the 13 included studies, supplementing with vitamin D produced a weighted mean difference of 0.876 kg (95% CI = 0.180 to 1.571, P = 0.014, I2 = 68.5%) for handgrip strength (HGS), a measurement of muscle strength. However, an insignificant decrease in time was obtained after analyzing of 0.044 s (95% CI =-0.979 to 0.892, P = 0.927, I2 = 95%) to complete the timed up and go test (TUG). According to subgroup analysis, vitamin D supplementation increased HGS in patients over the age of 60 (P = 0.001), and in those without calcium supplementation (P = 0.032), as well as in those whose baseline vitamin D level was greater than 75 nmol/L (30 ng/ml) (P = 0.003). Conclusion:Taking into account the studies in this systematic review, vitamin D supplementation improved muscle strength in postmenopausal women. However, an insignificant result was demonstrated in terms of mobility after vitamin D supplementation.